Dampak Kualitas Pendidikan Dan Kemampuan Diri Terhadap Keputusan Siswa Memilih Program Pendidikan Islam Di Perguruan Tinggi: Menjelajahi Peran Mediasi Brand Image - Harni Soimah; Safiruddin al Baqi; Rihab Wit Daryono (Program Studi Manajemen Pendidikan, 2024)
Educational institutions that succeed in building a positive brand image, providing quality education, and supporting the development of student's self-ability will have an advantage in attracting prospective students and maintaining their loyalty. This research aims to explore the role of brand image as a mediator on the influence of educational quality, self-ability, and student decisions. The survey method was used to collect data based on probability sampling of 457 students of the 2021 IAIN Ponorogo Islamic Religious Education study program. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis was used to analyze data and test the conceptual model. The results of the analysis show that the quality of education does not have a significant effect on students' decisions to choose the Islamic Religious Education study program. These findings emphasize the importance of strengthening the brand image of educational institutions as a mediator that influences the relationship between educational quality, self-ability, and student decisions. Therefore, educational institutions need to pay attention to strategies to strengthen their brand image in order to increase their attractiveness in the eyes of prospective students and provide a more meaningful educational experience.